Association Between Selected Socio Demographic Variables and Musculoskeletal Symptoms Experienced By Dentists in a Southern Karnataka District - Shaik, AB; Rao, BH Sripathi; Husain, A; D'Sa, JL (Kathmandu University Medical Journal, 2013)
Background The majority of working dentists experience some type of musculoskeletal discomfort during the course of their professional career. The prevalence and location of musculoskeletal symptoms are influenced by work habits, postures adopted by dentists while performing their professional work and socio demographic variables. Objectives The current study was carried out to find the association between musculoskeletal symptoms experienced by dentists and selected socio demographic variables in a southern Karnataka district. Methods For this study 300 dentists were selected by using convenience sampling method among post graduate dental students, faculty members and private practitioners with more than one year of experience from in and around Mangalore city. In order to find the association, a pre-tested, self-administered questionnaire - Musculoskeletal Disorder Rating Scale was used. Results The study showed that there was statistically significant association between frequency of pain and average patient(s) treated per day. The association between intensity of pain and average patient(s) treated per day was highly significant. Further there was a significant association between intensity of pain and field of dental practice. With regard to the field of dental practice, frequency of stiffness was significantly associated with the age. The association between frequency of stiffness and no. of year(s) in profession was highly significant. Conclusion The study revealed a significant association between musculoskeletal symptoms experienced by the dentists and socio demographic variables like; age, field of dental practice, no. of years in profession and average patients treated per day. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 9-13 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7335